2002
DOI: 10.1111/1467-7717.00192
|View full text |Cite
|
Sign up to set email alerts
|

Forced Migration, Processes of Return and Livelihood Construction among Pastoralists in Northern Sudan

Abstract: The Hawaweer, a nomadic, pastoralist group in northern Sudan, were seriously affected by the drought in the Sahel during the mid-1980s. Their experience illustrates the connection between internally displaced people, normal mobility, forced migration, dilemmas and opportunities of return and how new livelihoods can be successfully constructed based on traditional rights, strong local institutions and external resources. Some displaced Hawaweer got the chance to return to their homeland as new livelihood opport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 11 publications
1
21
0
Order By: Relevance
“…However, with little moisture, households can sustain their family by growing crops. This reiterates the argument in the secondary literature that farming serves as a coping strategy (Haug 2002). In Mieso, although crop farming and livestock keeping are equally perceived to contribute to household food security, there exists an increasing trend of diminishing grazing land (feed scarcity), which has severely affected the livestock population and its productivity.…”
Section: Determinants Of Food Securitysupporting
confidence: 61%
“…However, with little moisture, households can sustain their family by growing crops. This reiterates the argument in the secondary literature that farming serves as a coping strategy (Haug 2002). In Mieso, although crop farming and livestock keeping are equally perceived to contribute to household food security, there exists an increasing trend of diminishing grazing land (feed scarcity), which has severely affected the livestock population and its productivity.…”
Section: Determinants Of Food Securitysupporting
confidence: 61%
“…The return of pastoralists to northern Sudan following the mid 1980s Sahelian drought, for example, was highly skewed, with some displaced people returning at the first opportunity, whilst others were permanently displaced without access to resources (Haug, 2002). Groen and Polivka (2010) show how the rate of return of displaced people to New Orleans following Hurricane Katrina was strongly influenced by age, income and severity of damage, with the old and poor from severely damaged neighbourhoods slowest to return.…”
Section: Environmentalmentioning
confidence: 99%
“…According to the Intergovernmental Panel on Climate Change, "Most displaced people attempt to return to their original residence and rebuild as soon as practical" 3 . This finding, supported by studies on natural disasters from various parts of the world [4][5][6] , played an important and very necessary role in deflating popular fears 6 that in the future growing flows of environmental refugees (displaced by climate change) could end up swamping receiving regions. At the same time, a significant body of research identified displaced populations that found it unduly difficult to return.…”
mentioning
confidence: 86%